2021
DOI: 10.1097/gme.0000000000001845
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal CO2 laser therapy versus sham for genitourinary syndrome of menopause management: a systematic review and meta-analysis of randomized controlled trials

Abstract: Importance:The research of new therapeutic modalities, especially with energy-based devices, has been increasing nowadays for genitourinary syndrome of menopause (GSM) management. Microablative fractional CO2 laser has been used for pelvic floor dysfunction management.Objective:To conduct a systematic review and meta-analysis of randomized controlled trials to compare fractional CO2 laser therapy versus sham therapy for GSM management.Evidence Review:We searched for the available randomized clinical trials in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 35 publications
2
32
2
Order By: Relevance
“…Together, these results imply that vaginal CO 2 laser therapy does not induce thickening of the vaginal epithelium and thereby is ineffective in the treatment of GSM. Contrarily, multiple clinical trials have demonstrated significant improvement in experienced symptoms (dryness, burning, itching, dysuria, and dyspareunia) and sexual satisfaction 20 . Hence, there seems to be a discrepancy between these clinical trials and our findings.…”
Section: Discussioncontrasting
confidence: 86%
“…Together, these results imply that vaginal CO 2 laser therapy does not induce thickening of the vaginal epithelium and thereby is ineffective in the treatment of GSM. Contrarily, multiple clinical trials have demonstrated significant improvement in experienced symptoms (dryness, burning, itching, dysuria, and dyspareunia) and sexual satisfaction 20 . Hence, there seems to be a discrepancy between these clinical trials and our findings.…”
Section: Discussioncontrasting
confidence: 86%
“…A systematic review of three sham-controlled trials [13][14][15] for 82 women undergoing 3 monthly CO 2 laser treatments demonstrated improvement in the Vaginal Assessment Score of −0.49 and the FSFI of 9.37 4 weeks after treatment. 16 A sham-controlled trial with a 6-mo follow-up studied 30 women, and there were no differences in the proportion improved (64% vs 67%) and no differences in scores in the Vaginal Health Index, the VAS, the modified global assessment (PGI-I), the FSFI, the Day-to-Day Impact of Vaginal Aging, or the Urinary Distress Inventory short-form. 17 However, a longer-term sham-controlled trial with 1 y of follow-up in which 85 women received 3 monthly CO 2 laser treatments showed no improvement in vaginal symptoms by VAS or the Vulvovaginal Symptom Questionnaire score.…”
Section: Genitourinary Syndrome Of Menopausementioning
confidence: 95%
“…Energy-based therapies include fractional CO 2 laser or erbium YAG laser and radiofrequency devices; however, none of these approaches has received FDA approval due to safety concerns [18]. Although clinical studies have shown benefit and safety [148][149][150], recent experimental data and data from randomized controls trials question the efficacy of laser treatment [151,152].…”
Section: Laser Therapymentioning
confidence: 99%